Glory and terror seven deaths under the French Revolution - Baecque, Antoine de 1962- (Routledge, 2001)
"Fully engaging our fascination with the macabre, Glory and Terror illustrates how certain corpses became highly charged political symbols during the course of the French Revolution. Arguing that the key moments of the Revolution were "dialogues with the dead," this study dramatically evokes the passions inflamed by seven famous corpses. Antoine de Baecque takes a look at the very public death of the great orator and libertine, Mirabeau; describes the pageantry of the procession carrying Voltaire's body to the Pantheon; and investigates the sexually-charged myths surrounding the murder of Marie Antoinette's intimate friend, the Princesse de Lamballe. He recreates the tense and awe-inspiring spectacle of Louis XVI's execution, and examines the agonizing final hours of the defeated and disfigured Robespierre."--BOOK JACKET.